Lysophosphatidic acid in atherosclerotic diseases - Schober, Andreas (Blackwell Publishing Ltd, 2012)
Lysophosphatidic acid (LPA) is a potent bioactive phospholipid. As many other biological active lipids, LPA is an autacoid: it is formed locally on demand, and it acts locally near its site of synthesis. LPA has a plethora of biological activities on blood cells (platelets, monocytes) and cells of the vessel wall (endothelial cells, smooth muscle cells, macrophages) that are all key players in atherosclerotic and atherothrombotic processes. The specific cellular actions of LPA are determined by its multifaceted molecular structures, the expression of multiple G-protein coupled LPA receptors at the cell surface and their diverse coupling to intracellular signalling pathways. Numerous studies have now shown that LPA has thrombogenic and atherogenic actions. Here, we aim to provide a comprehensive, yet concise, thoughtful and critical review of this exciting research area and to pinpoint potential pharmacological targets for inhibiting thrombogenic and atherogenic activities of LPA. We hope that the review will serve to accelerate knowledge of basic and clinical science, and to foster drug development in the field of LPA and atherosclerotic/atherothrombotic diseases.